2011
DOI: 10.1180/minmag.2011.075.4.2401
|View full text |Cite
|
Sign up to set email alerts
|

A review of analogues of alkaline alteration with regard to long-term barrier performance

Abstract: Cement and concrete will be used as fracture grouts, shotcrete, tunnel and borehole seals, and as matrices for waste encapsulation inter alia in geological repositories for radioactive wastes. Alteration of the host rock and/or swelling clay in waste package buffers and tunnel backfills by hyperalkaline solutions from cement/concrete may be deleterious to system performance through changes in the physicochemical properties of these barrier materials.Analogue systems (and timescales) relevant to the understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 74 publications
1
35
0
Order By: Relevance
“…One of the main purposes of the cement is to maintain high pH conditions (>pH 12.5) that will reduce radionuclide solubility and microbial activity. Cement-equilibrated water will migrate into the surrounding host rock forming a plume of elevated pH, alkaline water, forming a region known as the 'alkaline disturbed zone' (ADZ) (Atkinson, 1995;Savage, 1995Savage, , 2011. The pH of the cement porewater and of the alkaline plume will decrease over time (Atkinson, 1985;Baston et al, 2012) as differing cement components buffer the pH (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main purposes of the cement is to maintain high pH conditions (>pH 12.5) that will reduce radionuclide solubility and microbial activity. Cement-equilibrated water will migrate into the surrounding host rock forming a plume of elevated pH, alkaline water, forming a region known as the 'alkaline disturbed zone' (ADZ) (Atkinson, 1995;Savage, 1995Savage, , 2011. The pH of the cement porewater and of the alkaline plume will decrease over time (Atkinson, 1985;Baston et al, 2012) as differing cement components buffer the pH (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Thomassin and Rassineux, 1992;Savage 2011). Predictive computer modelling is one way to achieve this, but the outputs from such modelling are highly dependent upon the databases used, and the codes may not adequately represent the complexities of real systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pertinent to this study, examination of cements in historic structures and natural systems, such as Maqarin in Jordan and a number of saline lakes, have been studied as analogues for high-pH mineral alteration (Tinseau et al, 2006;Techer et al, 2012;Hodgkinson and Hughes, 1999;Milodowski et al, 1998;Surdam, 1977;Taylor andSurdam, 1981, in Savage, 2010;Chermak, 1992Chermak, , 1993. These studies have also shown high pH causes silicate mineral dissolution and secondary C-S-H phase formation but also suggest that over long timescales (10 s to 10 6 years) C-S-H may evolve to Kfeldspars or zeolites (Savage, 2011). However, analogue systems are generally poorly constrained and increasing the number of sites studied is important to increase confidence in their applicability to CDZ scenarios (McKinley and Alexander, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies are necessarily short in timscale with few lasting longer than 1-2 years (Gaucher and Blanc, 2006;Fernandez et al, 2010;Moyce et al, 2014). To improve understanding of the potential mineral alteration processes at longer timescales, high-pH systems in the natural and anthropogenic analogues have also been studied (IAEA, 1989;Miller et al, 2000;Savage, 2011). Pertinent to this study, examination of cements in historic structures and natural systems, such as Maqarin in Jordan and a number of saline lakes, have been studied as analogues for high-pH mineral alteration (Tinseau et al, 2006;Techer et al, 2012;Hodgkinson and Hughes, 1999;Milodowski et al, 1998;Surdam, 1977;Taylor andSurdam, 1981, in Savage, 2010;Chermak, 1992Chermak, , 1993.…”
Section: Introductionmentioning
confidence: 99%